Longitudinal effects of coping on outcome in a randomized controlled trial of a group intervention for HIV-positive adults with AIDS-related bereavement. - Hansen, Nathan B; Tarakeshwar, Nalini; Ghebremichael, Musie; Zhang, Heping; Kochman, Arlene; Sikkema, Kathleen J (Death studies, 2006)
This study examined the longitudinal effects of coping on outcome one year following completion of a randomized, controlled trial of a group coping intervention for AIDS-related bereavement. Bereaved HIV-positive participants (N = 267) were administered measures of grief, psychiatric distress, quality of life, and coping at baseline, post-intervention, and at 4-, 8-, and 12-month follow-ups. Coping strategies directly impacted all outcome variables for both study conditions. Additionally, the coping intervention moderated the relationship between avoidant coping and the longitudinal course of grief and psychiatric distress, resulting in greater reductions in grief and distress for intervention participants after accounting for avoidant coping strategies.
Keywords: Acquired Immunodeficiency Syndrome; Adaptation, Psychological; Adult; Bereavement; Ethnic Groups; Female; Grief; HIV Seropositivity; Humans; Longitudinal Studies; Male; New York; Psychotherapy, Group; Quality of Life; Randomized Controlled Trials as Topic; Sexual Behavior; Time Factors; Treatment Outcome; United States; Wisconsin